2018
DOI: 10.1080/14664208.2018.1495370
|View full text |Cite
|
Sign up to set email alerts
|

The community as a language planning crossroads: macro and micro language planning in communities in Wales

Abstract: This paper teases out the meeting points between macro and micro language planning in Wales and how this impacts upon community language use in real terms. The paper draws upon data gathered from an evaluation of the Welsh Government's strategy towards the maintenance and promotion of the Welsh language on a community level in Wales. Conducting this research provides an insight into how the community acts as a language planning crossroads where a plethora of factors contribute to language use within this spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Indeed, Hodges and Prys (2019, 1) emphasise the importance of the community beyond the education sector as a 'language planning crossroads' that brings the different influences of linguistic behaviour together. Hodges and Prys (2019) also point to the importance of studying micro-level community linguistic interactions which could provide further insight into new speakers' linguistic daily practices beyond education. Research into new speakers however, can also influence language policies on a macrolevel (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Hodges and Prys (2019, 1) emphasise the importance of the community beyond the education sector as a 'language planning crossroads' that brings the different influences of linguistic behaviour together. Hodges and Prys (2019) also point to the importance of studying micro-level community linguistic interactions which could provide further insight into new speakers' linguistic daily practices beyond education. Research into new speakers however, can also influence language policies on a macrolevel (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a slight increase recorded a decade later (20.8%), the 2011 Census indicated that only 19% of the population declared having skills in the language. Several factors are claimed to have influenced such results, including the methodology employed (Hodges & Prys, 2019). At the time of writing of this article, the results of the 2021 Census are not available.…”
Section: Demographics and The Welsh Languagementioning
confidence: 99%
“…After decades of slow legitimation and institutionalisation of Welsh driven for the most part by language activism (May, 2000, pp. 105-111), the Welsh Language (Wales) Measure was passed in 2011, giving the Welsh language an official status in Wales (Hodges & Prys, 2019).…”
Section: Wales Its Population and The Welsh Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Despite this notion having contributed to a large volume of earlier language policy and planning (LPP) studies, it was challenged by Kaplan and Baldauf [2], who claimed that LP could occur on other societal levels, e.g., the meso-and micro-level. Since then, there has been an increasing amount of research investigating micro-level contexts, such as family [3,4], speech communities [5,6], and educational settings [7,8], as the sites for LP [see 9 for a review]. Nevertheless, as Liddicoat [10] highlighted, although local actors assume agency in creating micro language policies, the consideration of their agency in the LPP research comes fairly recently and remains scarce in number.…”
Section: Introductionmentioning
confidence: 99%